Pre-surgery briefings and safety climate in the operating theatre. Issue 8 (14th June 2011) - Allard, Jon; Bleakley, Alan; Hobbs, Adrian; Coombes, Lee
Abstract : Background: In 2008, the WHO produced a surgical safety checklist against a background of a poor patient safety record in operating theatres. Formal team briefings are now standard practice in high-risk settings such as the aviation industry and improve safety, but are resisted in surgery. Research evidence is needed to persuade the surgical workforce to adopt safety procedures such as briefings. Objective: To investigate whether exposure to pre-surgery briefings is related to perception of safety climate. Methods: Three Safety Attitude Questionnaires, completed by operating theatre staff in 2003, 2004 and 2006, were used to evaluate the effects of an educational intervention introducing pre-surgery briefings. Results: Individual practitioners who agree with the statement 'briefings are common in the operating theatre' also report a better 'safety climate' in operating theatres. Conclusions: The study reports a powerful link between briefing practices and attitudes towards safety. Findings build on previous work by reporting on the relationship between briefings and safety climate within a 4-year period. Briefings, however, remain difficult to establish in local contexts without appropriate team-based patient safety education. Success in establishing a safety culture, with associated practices, may depend on first establishing unidirectional, positive change in attitudes to create a safety climate.